FAKTOR YANG MEMPENGARUHI MINAT SISWA UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA SMK NEGERI 1 PANGKALAN KURAS - Atika Nur Aini; Gimin Gimin; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of Peers Environment and Conditions of Sosial and Economics Parent to students’ interest to continue their education to the university on students SMK Negeri 1 Pangkalan Kuras. The sample of the in this research were 54 respondents determined with the formula slovin to technique the sample collection using a technique random sampling. The result of this research is the Peers Environment have a significant effect on the Students’ interest students’ interest result which is obtained tcount 4,017 <ttabel 2,008 and significant value 0,000 < 0,05. Conditions of sosial and economics parent have a positive and significant impact on Students’ interest outcomes where obtained tcount 4,895 > ttabel 2,008 and significant value 0,000 < 0,05. In silmutan there is a positive or significant influence between Peers Environment and Conditions of Sosial and Economics Parent with Students’ interest fcount 29,249 > ftabel 3,179 and significant value 0,000 < 0.05. The result of multiple regression research found that the Peers Environment, Conditions of Sosial and Economics Parent have a significant effect on the students' interest outcomes of 53,4% and the rest of 46,6% influenced by other factors outside this study.Key Words: Peers Environment, Conditions of Sosial and Economics Parent andStudents’ interest